Study of the Incidence of Some Chronic Diseases Among patients with Long-term Physical Disabilities - Alekova Todorova, Sevdalina (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: People living in old age with disabilities acquired in early adulthood or because of a congenital anomaly represent a growing population with unique medical needs. This study aims to investigate the incidences of chronic diseases and the prevalence of chronic polymorbidity among adults with physical disabilities, who are accommodated in the largest social home on the Balkan Peninsula. Methods: In this descriptive survey, 179 people with physical disabilities were studied during 2017- 2018. A structured questionnaire was used to obtain information on socio-demographic characteristics, personal lifestyle and self-reported diagnosis of the presence of chronic diseases. In addition to the above, second research was conducted on the available medical documentation for the health status of each person, which helped to verify the information about the incidence and prevalence of chronic diseases among adults with physical disabilities. Results: Most of the adults with physical disabilities have at least more than two chronic conditions (69.27 %). Arterial hypertension is the commonest chronic illness among them (47. 48 %). The study reported a raised incidence of chronic diseases of the digestive system and chronic diseases of the urinary system, as well as increasing prevalence of diabetes mellitus type II, chronic diseases of the pulmonary system and degenerative joints diseases correlated with the age of persons. Conclusion: The study showed an increased frequency of chronic diseases among adults with physical disabilities and a significant number of persons who have multiple chronic conditions, which determines the need for frequent and long-term health care.